Short Communication: Larvicidal and antifeedant activities of Kalanchoe daigremontiana against Plutella xylostella larvae - DEWI HIDAYATI; YUDI DARMANTO; TUTIK NURHIDAYATI; NURLITA ABDULGANI (Nusantara Bioscience, 2016)
Abstract. Hidayati D, Darmanto Y, Nurhidayati T, Abdulgani N. 2016. Short Communication: Larvicidal and antifeedant activities of Kalanchoe daigremontiana against Plutella xylostella larvae. Nusantara Bioscience 8: 312-315. Larvicidal and antifeedant activities of Kalanchoe daigremontiana polar extract were tested on fourth instar of Plutella xylostella larva using choice test, leaf dipping method and antifeedant capacity test (no choice test). K. daigremontiana polar extract in level of 0.25, 0.5, 0.75, 1, 1.25, and 1.5% were used on choice test to determined the larvae behavior tendencies of an attractant or to be an antifeedant, while on toxicity test were used extract in level of 0.25% and 0.5%, whereas on antifeedant capacity test were in level of 0.75, 1, 1.25, and 1.5%. The Probit analysis resulted that 50% of lethal concentration (LC50) was found at 72 hours exposure of 0,5% polar extract. Effective concentration for antifeedant at 1.25%, while antifeedant capacity percentage was in level of 84.85%.